Pulsed ion beam formation of highly doped GaAs layers; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 139, iss. 1-4 - Bayazitov R. M.; Antonova L.Kh.; Khaibullin I. B.; Remnev G. E. Gennady Efimovich (1998, 1998)
Title screen